Um estudo sobre o comprometimento vocacional na construção das trajetórias de carreira de gestores e docentes do Ensino Superior - Alencar, Olivia Lima Guerreiro de (2012)
In this research, we consider vocation as a dimension of career commitment and we deepen the understanding of its representation in the construction of the trajectories of professional life. We seek to know how vocationally committed individuals build their careers nowadays. The conceptual framework comes from Donald Super’s vocational psychology and from the concept of "protean career" by Douglas Tim Hall, whose concepts point to a developmental-contextual perspective of the career construction. We adopted a qualitative and quantitative data treatment with the application of the scale of commitment and entrenchment in a sample of 34 individuals of both sexes, from a high education institution, both teachers and/or managers. Individuals with higher scores in the range of career commitment were interviewed individually and the data subjected to content analysis. The following psychological dimensions were considered: self-concept of vocation, career planning, meaning of work, social influences, choice of profession and identification with the current job. The results indicate a significant relationship between family relationships, self concept, career planning among the vocationally committed individuals. A career as a vocation seems to have been experienced and known in the context of an intimate family circle, where the individual developed the first elements of self-concept and vocational decisions. The families showed common traits in the relationship between parents and children: autonomy for vocational decision, the support to do it and valuing the work as a major means of obtaining satisfaction in life. It was found that the subject vocationally involved received references of a protean career model through his family figures with which they identified themselves. One of the most relevant dimensions found in the subjects of this research relates to career management: they are autonomous and their decisions are guided by vocational self-concept that gives them a clear and significative sense of orientation to the working life. The perspective of the vocational commitment with the career is discussed both in a theoretic and in a practical basis as a proposed type of protean career based on the colected informations.